The Influence Of Tpack Model And Collaborative Learning Towards Bisha City Secondary Schools’ Teacher Teaching Quality On The Use Of Mobile Learning Professional Development - Alaklubi, Mohammed Theeb A (2024)
The research aims to identify the influence of the content, pedagogical, technological knowledge (TPACK), and collaborative learning on teaching quality in the application of m-learning for the professional development of Saudi secondary school teachers. In this study, the quantitative method was used, and the respondents consisted of 282 teachers from Saudi secondary schools in Bisha City. Hence, the research findings aim to contribute to the work of policymakers, teachers, practitioners, and future researchers on improving the quality of teaching. The data collection, the researcher, constructed an online survey in Google Forms in Google Drive. The method involved using simple random sampling techniques to select respondents to the quantitative approach to produce statistical data. To analyze the data, the researcher applied the SPSS version 26 methodology to examine the relationship between variables using Pearson's correlation, in addition to analyzing quantitative data using descriptive analysis based on mean, frequencies, and percentages. The results of this study reported that teachers in Saudi Arabia do have positive perceptions toward the influence of content, technological and pedagogical knowledge, and collaborative learning in teaching quality for the use of m-learning for PD in Bisha City secondary schools.